Performance analysis and enhancement for the current and future IEEE 802.11 MAC protocols. - Xiao, Yang
The IEEE 802.11 specifications provide up to 54 Mbps data rates, respectively. The industry is seeking Higher Data Rates (HDR's) over 100Mbps for IEEE 802.11a extension. However, the medium access control (MAC), which they are based upon, is the same. In this paper, we explore the overhead of HDR's to find out whether the MAC is good enough for the increasing data rates and what to expect as the industry seeks higher data rates. We prove that a theoretical throughput upper limit and a theoretical delay lower limit exist for IEEE 802.11 protocols. The existence of such limits indicates that the overhead must be reduced to get good performance for HDR's. Otherwise, the enhanced performance of HDR's is limited and bounded even when the data rate becomes infinitely high. Both reducing overhead and pursuing HDR's are therefore necessary and important. In order to reduce overhead, we propose a burst transmission and acknowledgement (BTA) mechanism, in which, instead of acknowledging each frame, a burst of frames is received first, and then the whole burst is acknowledged one time. Our study shows that with the BTA mechanism, overhead has been greatly reduced and performance has been greatly improved.